Application of the PSO–neural network in rainfall–runoff modeling. Issue 1 (14th December 2022) - Kumar, Keshav; Singh, Vivekanand; Roshni, Thendiyath
Abstract: In this study, rainfall–runoff (R–R) models were developed by assembling Particle Swarm Optimization (PSO) with the Feed Forward Neural Network (FFNN) and the Wavelet Neural Network (WNN). Performances of the model were compared with the wavelet ensembled neural network (WNN) and the conventional FFNN. The data from 1981 to 2005 were used for calibration and from 2006 to 2014 for validation of the models. Different combinations of rainfall and runoff were considered as inputs to the PSO–FFNN model. The fitness value and computational time of all the combinations were computed. Input combination was selected based on the lowest fitness value and lowest computational time. Four R–R models (FFNN, WNN, PSO–FFNN and PSO–WNN) were developed with the best input combination. The performance of the models was evaluated using statistical parameters (Nash–Sutcliffe Efficiency ( NSE ), D and root mean square error ( RMSE )) and parameters vary in the range of (0.86–0.90), (0.95–0.97) and (68.87–84.37), respectively. After comparing the performance parameters and computational time of all four models, it was found that the PSO–FFNN model gave better values of NSE (0.89), D (0.97), RMSE (68.87) and less computational time (125.42 s) than other models. Thus, the PSO–FFNN model was better than the other three models (FFNN, WNN and PSO–WNN). HIGHLIGHTS: The goals of this research are selection of input combination based on fitness value and computational time. Four R-R models (FFNN, WNN, PSO-FFNN and PSO-WNN) were developed with the best input combination. The performance of the models was evaluated using statistical parameters (NSE, D and RMSE).